Moving Forward : How Indonesia’s Districts Reduce Stunting - World Bank (Washington, DC, 2022)
This new publication "Moving Forward: How Indonesia's Districts Reduce Stunting" is part of a series which follows the flagship publication “Aiming High: Indonesia’s Ambition to Reduce Stunting” published in 2018. This new publication introduces some of the most promising local nutrition initiatives and lessons learned that have helped to reduce stunting. The book aims to document such initiatives for knowledge sharing and provide lessons learned for the operationalization of stunting prevention strategy in Indonesia at all levels.